New heinemann maths 5 extension textbook - Blair, John T. (Heinemann Harlow, 2001)
The ideal resource to stimulate your pupils$1 (Bnumerical thinking. A child-friendly textbook which reinforces fluency in number facts and provides problem-solving activities.s